Nazwy pomieszczeń w dworach szlacheckich - Świtała-Cheda, Mirosława (Acta Universitatis Lodziensis. Folia Linguistica, 2014)
Architectural and functional transformations of noblemen’s mansion houses present an extremely appealing subject for a linguist as they convey very rich vocabulary. The article describes how the residents of mansion houses “organized” their living space. I would like to focus particularly on the lexis which served as a means to outline this space. I examine its structure and etymology. The excerpted sources of the material (the names of the interiors, edifices and less frequently isolated spaces) are rural self-help books from the 19th century, mansion’s inventories and architectural maps from the 16th – 19th centuries. The accumulated vocabulary depicts changing needs of a human being.